Resilience, stress, and coping among Canadian medical students - Rahimi, Behruz; Baetz, Marilyn; Bowen, Rudy; Balbuena, Lloyd (Revue canadienne de l'éducation médicale, 2014)
Background: Numerous studies have established that medical school is a stressful place but coping styles and resilience have not been adequately addressed as protective factors. Method: Using a cross-sectional design, 155 students were surveyed using the Connor-Davidson Resilience Scale, Perceived Stress Scale, and the Canadian Community Health Survey Coping Scale. Mean scores were compared by gender and between our sample and normative scores using t-tests. Multivariate linear regression was performed to examine whether stress levels were related to coping and resilience. Results: Medical students had higher perceived stress, negative coping, and lower resilience than age and gender-matched peers in the general population. Male medical students had higher positive coping scores than general population peers and higher resilience, and lower perceived stress than female medical students. Coping scores did not vary by gender in our sample. The multivariate model showed that resilience and negative, but not positive coping, predicted stress. Conclusions: Medical students are neither more resilient nor better equipped with coping skills than peers in the population. Greater emphasis on self-care among medical trainees is recommended. Emphasizing the importance of self-care during medical training, whether by formal incorporation into the curriculum or informal mentorship, deserves further study.